Financial inclusion and the informal sector - Rojas Cama, Freddy (2024)
This paper explores the relationship between the informal sector and financial inclusion for a sample of 186 countries across the period 2004–2018 by using various methods of estimations—ordinary least squares, instrumental variables, fixed effects, and general method of moments. The results show financial inclusion significantly reduces the size of the shadow economy throughout indicators of access and usage of financial services. The results are also robust when controlling by income level, these results strongly support the use of financial inclusion as an effective vehicle to lessen informality. Our policy recommendations are directed towards improving financial infrastructure and fostering inclusive financial environments to effectively decrease informality. Adopting dynamic, long-term strategies to sustain financial inclusiveness is key to achieving lasting reductions in the informal sector.